7(2x+1)-2x=3(4x+1)+4

Simple and best practice solution for 7(2x+1)-2x=3(4x+1)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2x+1)-2x=3(4x+1)+4 equation:


Simplifying
7(2x + 1) + -2x = 3(4x + 1) + 4

Reorder the terms:
7(1 + 2x) + -2x = 3(4x + 1) + 4
(1 * 7 + 2x * 7) + -2x = 3(4x + 1) + 4
(7 + 14x) + -2x = 3(4x + 1) + 4

Combine like terms: 14x + -2x = 12x
7 + 12x = 3(4x + 1) + 4

Reorder the terms:
7 + 12x = 3(1 + 4x) + 4
7 + 12x = (1 * 3 + 4x * 3) + 4
7 + 12x = (3 + 12x) + 4

Reorder the terms:
7 + 12x = 3 + 4 + 12x

Combine like terms: 3 + 4 = 7
7 + 12x = 7 + 12x

Add '-7' to each side of the equation.
7 + -7 + 12x = 7 + -7 + 12x

Combine like terms: 7 + -7 = 0
0 + 12x = 7 + -7 + 12x
12x = 7 + -7 + 12x

Combine like terms: 7 + -7 = 0
12x = 0 + 12x
12x = 12x

Add '-12x' to each side of the equation.
12x + -12x = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 12x + -12x

Combine like terms: 12x + -12x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| X^2(X^2-8x+7)= | | 68=5x+8 | | 2x+3=-6x+-37 | | -9y+6+2y=-17 | | 2(2x+9)=2(2x+1)+2x | | 5(6+x)=4(x-2) | | 4x+7=-6+47 | | 2(4x+2)=7(x+6) | | 6x^6/2x^2y | | N-12=3x | | 5(3x+5)=4(3x+4)+3x | | 2(x+1)=7-5(2x+1) | | N-12=5x | | 2y+0x=4 | | 10s^2-s-s^2-16-3s+11= | | X^2+52x+100= | | 6(6v+6-5)=1+6r | | 2x-8=5x+(10) | | -12=5k-8 | | 4b-2b=20 | | x^2-30y+352=0 | | 4x+52=4(2x+8) | | 8y+7y=-75 | | (5x+1)(2x)= | | 2x+3=7x+(-42) | | 5x^4-12x^2+3=0 | | 3k=5k+7 | | -11+3x=x-15 | | 4.905x^2-4x-22=0 | | 2x^2-1528x+2821=0 | | 5p+14=29 | | m/4=2 |

Equations solver categories